A LITERATURE REVIEW OF MODIFICATION KALINA CYCLE APPLICATIONS AND ADVANCEMENTS (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
This literature review examines the applications and advancements of the Kalina cycle in the context of renewable energy growth. The Kalina cycle, an improvement on the traditional Rankine cycle, offers enhanced efficiency for power generation from low-grade heat sources. This review synthesizes recent research on Kalina cycle implementations in geothermal, solar thermal, and most waste heat recovery applications, such as industry, diesel engines, and marine engines, as well as contributions to the augmenting power, desalination process, and the field of cosmic space. Also, studying a binary solution as the working fluid and the reason for selecting the ammonia-water mixture; additionally, discussion of the issues of corrosion and material compatibility. Finally, mention the correlation core of thermodynamic properties for analysis of the Kalina cycle. The findings indicate that while the Kalina cycle shows promise for improving renewable energy utilization, further research and development are needed to address efficiency, cost, and implementation barriers.